Wheat leaf epidermal pattern as a model for studying the influence of stress conditions on morphogenesis - U. S. Zubairova; A. V. Doroshkov (Вавиловский журнал генетики и селекции, 2018)
The leaf epidermis of a monocotyledonous plant is a widely used model system for studying the differentiation of plant cells, as it contains readily observable specialized cells. The approach proposed in this paper uses a growing cereal leaf to study stress-induced dynamic changes in morphogenesis. In the process of formation, the linear leaf of wheat remains in the stationary growth phase for long. This fact permits us to observe a series of successive morphogenetic events recorded in the cellular structure of the mature leaf. In studying the cellular architecture of the wheat leaf epidermis, we obtained and processed confocal 3D images of wheat leaves stained with fluorescent dyes. This procedure allows an accurate morphometric description and determination of quantitative characteristics of the leaf epidermal pattern. Low temperatures are among the factors limiting the growing of crop plants in the temperate zone. In the present work, we show significant aberrations of stomatal morphogenesis in the epidermis of boot leaves of wheat varieties Saratovskaya 29 and Yanetskis Probat in response to cold stress. We found that nonfunctional stomata predominated in the zone of maximum manifestation of stress, whereas in the zones formed before and after the stress impact, the developmental anomalies come to the disturbance in the morphogenesis of subsidiary cells. In Saratovskaya 29, a significant amount of ectopic trichomes formed in rows predetermined to stoma formation. The proposed approach can provide standardized qualitative and quantitative data on stress-induced morphogenesis aberrations in wheat leaf epidermis. Subsequently, these data can be used for verification of computer models of leaf morphogenesis. Further study of the mechanisms of the effect of cold stress on morphogenesis will add to the search for additional opportunities to increase wheat yields in areas of risky agriculture.